2006
DOI: 10.1143/jjap.45.7444
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric and Dielectric Properties of (LiNaK)(NbTaSb)O3 Ceramics with Variation in Poling Temperature

Abstract: In this study, lead-free (LiNaK)(NbTaSb)O 3 piezoelectric ceramics were fabricated on the basis of the amount of K 2 CO 3 addition, and their piezoelectric and dielectric properties were investigated by varying the amount of K 2 CO 3 addition and poling temperature. First, to achieve optimum poling conditions for manufactured specimens, the poling temperature was varied to be 0, 20, 50, 80, and 110 C. The optimum poling temperature was 20 C. It was found that 0.1 wt % K 2 CO 3 -added (Li 0:04 Na 0:44 K 0:52 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 3 publications
(3 reference statements)
3
39
0
Order By: Relevance
“…Therefore, it is necessary to search for lead-free piezoelectric ceramics with excellent properties. Recently, much attention for lead-free piezoelectric ceramics has been paid to (K 0.5 Na 0.5 )NbO 3 (KNN)-based ceramics because of its environmental harmony, good electrical properties, and high Curie temperature [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to search for lead-free piezoelectric ceramics with excellent properties. Recently, much attention for lead-free piezoelectric ceramics has been paid to (K 0.5 Na 0.5 )NbO 3 (KNN)-based ceramics because of its environmental harmony, good electrical properties, and high Curie temperature [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is also found that the T c shifts upward, and T o-T shifts downward compared to pure KNN materials (T c ∼ 420 • C and T o-T ∼195 • C) owing to the addition of ALN, i.e., the T c shift upward, and T o-T shift to downward with the increase of ALN content. As compared with some KNN-based ceramics reported, it was clear that the results in present work show that the (1 − x)KNNL-xALN (x = 0.01) lead-free piezoelectric ceramics possess higher Curie temperature (T c = 476 • C), which is higher than the reported values of KNN-based ceramics [1][2][3][4][5][6][7][8][9]. In this work, high Curie temperature and good piezoelectric properties of (1 − x)KNNL-xALN ceramics are attributed to Ag and Li cosubstitution.…”
Section: Resultsmentioning
confidence: 41%
“…Recently, much attention for lead-free piezoelectric ceramics has been paid to (K 0.5 Na 0.5 )NbO 3 (KNN) based piezoelectric ceramics for its good electrical properties and high Curie temperature [4][5][6][7][8][9][10][11][12][13][14][15][16]. But recent research results also reveal that the piezoelectric properties of KNN-based lead-free ceramics could be improved, but the Curie temperature (T c ) of the ceramics usually decreases [4][5][6][7]10,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inferior ferroelectric response is obtained by insufficient poling, which is caused by various factors such as defects. The effect of poling conditions on the dielectric and piezoelectric properties of KNN-based ceramics has been a subject of recent studies [92][93][94][95][96][97], most of which pointed out that poling temperature is of significant importance for property enhancement. Nevertheless, poling process could also be utilized to manipulate interior dipole movement, which might be tuned to favorable piezoelectric performance [52,53].…”
Section: Poling Tricksmentioning
confidence: 99%